Determination of standard time with the stopwatch time study method at PT BI - Ramadhan, Anas Anugerah; ⁠Sukanta, ⁠Sukanta; Fitriyani, Risma (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
In the manufacturing industry, the effectiveness of the work process is one of the key factors to increase the efficiency and competitiveness of the company. One of the main challenges is the accurate determination of standard working times, especially in processes involving manual inspections. Without a clear standard time standard, setting work targets is often not optimal, which can result in uneven workload, decreased productivity, and worker fatigue. PT BI is an automotive component manufacturing company that uses cold forging technology. One of the important processes in this company is visual inspection to guarantee product quality. However, the company does not yet have a standard time standard in the visual inspection process, so the daily target is determined based on the cycle time, which is less effective. This study aims to analyze the effectiveness of operators in using standard time in achieving targets. The study used the stopwatch time study method to measure the work cycle time in visual inspection operators. Data was collected through observations and interviews with operators as well as analysis using Minitab software. The results of the study show that the application of standard time is able to increase the effectiveness of operators in achieving daily targets. In addition, precise determination of standard timing provides companies with advantages with better process efficiency and reduced operator fatigue levels. In conclusion, the application of standard time can be the optimal solution to increase company productivity while maintaining worker welfare.